Participating Stakeholders in Decision Making of Tertiary Institutions in Nigeria as Panacea for Tertiary Education Development in Nigeria - Jacob Ogunode, Niyi; Iyabode Omolola, Afolabi; Doris Ugo-onyeka, Okani (Research Parks Publishers, 2025)
This paper looked at the benefits of participating stakeholders in the decision-making of tertiary institutions in Nigeria. The paper is a position paper that depends on secondary data. The secondary data were collected from online and print publications. The paper identified a stable academic environment, effective implementation of tertiary education goals, quality tertiary education and job satisfaction, and adherence to democratic principles, as those things that lead to substantive decisions and outcomes and lead to accountability and transparency in the system as benefits of participating stakeholders in the decision making of tertiary institutions in Nigeria. The paper concluded that the participation of stakeholders in the decision-making of tertiary institutions in Nigeria is vital to the realization of tertiary education goals in Nigeria. The paper recommends that the government and the agencies in charge of tertiary education management in Nigeria should ensure stakeholders in the Nigerian tertiary institutions are always engaged and consult before making policies and taking a decision that directly and indirectly affects the operation and welfare of the staff in the tertiary institutions in Nigeria.